1996
DOI: 10.1006/cbir.1996.0029
|View full text |Cite
|
Sign up to set email alerts
|

An Icam‐1 Like Cell Adhesion Molecule Is Responsible for Cd34 Positive Haemopoietic Stem Cells Adhesion to Bone‐marrow Stroma

Abstract: The epidermal keratinocytes express two major pairs of keratin polypeptides. One pair (K5/K14) expressed specifically in basal generative compartment and the other (K1/K10) expressed specifically in the differentiating suprabasal compartment. The switch in the expression of the keratins from proliferating to differentiating compartment indicates the changes that occur in the keratin filament organization which in turn influences the functional properties of the epidermis. Proper regulation of keratin gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Epidermal keratinocytes express two major pairs of keratin polypeptides, K5/K14 and K1/K10. K5/K14 is expressed specifically in the basal generative compartment and K1/K10 specifically in the differentiating suprabasal compartment [ 34 ]. Previous reports have shown that psoriatic epidermis contains lower amounts of K10 and higher amounts of K14 and K16 [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal keratinocytes express two major pairs of keratin polypeptides, K5/K14 and K1/K10. K5/K14 is expressed specifically in the basal generative compartment and K1/K10 specifically in the differentiating suprabasal compartment [ 34 ]. Previous reports have shown that psoriatic epidermis contains lower amounts of K10 and higher amounts of K14 and K16 [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because proper keratin gene expression and filament organization are absolutely necessary for normal functioning of the skin [26] and integrins are the main way by which cells both bind to and respond to their environment [27], the up-regulation of these classes of proteins could represent a mechanism for maintenance of functional properties of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…The lower expression of the adhesion molecule CD54 (ICAM-1) found on the CD34 1 cells in group III might impair interactions between these stem cells and stroma after the first steps of homing, as can be inferred from an earlier study (Rao et al, 1996).…”
Section: Discussionmentioning
confidence: 76%